Infrastructure profile and surrounding land use determine bird-train collision risk in a High-Speed Railway - Lourenço Falcão Rodrigues; Jesús Herranz Barrera; Eladio L. García de la Morena; Cristina Mata Estacio; Juan E. Malo (Global Ecology and Conservation)
High-Speed Railways (HSRs) are a growing transportation mode with significant environmental advantages, particularly in reducing carbon emissions. However, their direct impacts on wildlife, especially birds, are not fully understood. This study investigates the factors influencing bird-train collisions and risky bird crossings (crossings through the danger zone, defined as the 8.5-meter area between the railway tracks and the catenary) along a 300 km section of an HSR line in Spain. Using on-board video data, we recorded 675 bird risky crossing events over two years of data collection, totalling 127 journeys and 34,250 km of cumulative travel. Geographic Information System (GIS) data was used to explore three environmental factors affecting risky crossings and potential collision risks: (i) railway height (orography), (ii) surrounding landscape, and (iii) wildlife protected areas. Our findings reveal that certain HSR infrastructure features, such as the presence of tall embankments and surrounding landscape such as nearby open lands (crops and shrubland), significantly increase the frequency of risky crossings. Additionally, we found that species associated with human modified landscapes were particularly prone to these risky crossings, whereas forest birds were rarely observed performing risky crossings. These results highlight that birds’ collision risk is influenced by the biotic changes caused by the HSR. This research offers critical insights into the environmental impacts of HSRs on avian species, offering guidance for future infrastructure development and mitigation strategies.